2021
DOI: 10.1177/15347346211027684
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Results After Autologous Fat Transfer for Treatment of Chronic Lower Extremity Wounds

Abstract: Autologous fat transfer may offer a simple and effective treatment option for chronic wound patients, delivering adipose-derived stem cells, with potent regenerative attributes. Nevertheless, the clinical benefit has not yet been sufficiently demonstrated. A total of 39 wound patients were treated with autologous fat transfer (AFT) and matched with a control group, according to the identified confounding variables “gender” and “method of defect closure.” All data were acquired retrospectively. Primary outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Despite this limited number of available RCT's, the hypothesis of a temporary effect on wound healing and therefore an acceleration of the healing process seems to be evident and is supported by previous results of our working group 23 . Neovascularization is an important process in wound healing.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Despite this limited number of available RCT's, the hypothesis of a temporary effect on wound healing and therefore an acceleration of the healing process seems to be evident and is supported by previous results of our working group 23 . Neovascularization is an important process in wound healing.…”
Section: Discussionsupporting
confidence: 68%
“…Despite this limited number of available RCT's, the hypothesis of a temporary effect on wound healing and therefore an acceleration of the healing process seems to be evident and is supported by previous results of our working group. 23 Neovascularization is an important treatment of non-healing diabetic foot ulcers using a protocol with MSC application on Day 0 and again after 5 weeks. 24 They described the most pronounced absolute wound surface area reduction 2 weeks after each single application.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous clinical studies have reported that autologous fat grafting may accelerate healing in chronically scarred tissue resulting from chronic wounds and radiation-induced soft tissue injury [ 28 , 29 ]. In the field of burn treatment, fat grafting has shown promising outcomes as an adjuvant therapy by promoting wound healing, reducing the typical healing time, and minimizing the occurrence of hypertrophic scarring [ 30 ].…”
Section: The Pathophysiology Of Burn Wound Healingmentioning
confidence: 99%